All‐Silicon Broadband Ultraviolet Metasurfaces. Issue 38 (10th August 2018) - Deng, Yang; Wang, Xi; Gong, Zilun; Dong, Kaichen; Lou, Shuai; Pégard, Nicolas; Tom, Kyle B.; Yang, Fuyi; You, Zheng; Waller, Laura; Yao, Jie
Abstract: Featuring high photon energy and short wavelength, ultraviolet (UV) light enables numerous applications such as high‐resolution imaging, photolithography, and sensing. In order to manipulate UV light, bulky optics are usually required, and hence do not meet the fast‐growing requirements of integration in compact systems. Recently, metasurfaces have shown unprecedented control of light, enabling substantial miniaturization of photonic devices from terahertz to visible regions. However, material challenges have hampered the realization of such functionalities at shorter wavelengths. Herein, it is experimentally demonstrated that all‐silicon (Si) metasurfaces with thicknesses of only one‐tenth of the working wavelength can be designed and fabricated to manipulate broadband UV light with efficiencies comparable to plasmonic metasurface performance in infrared (IR). Also, for the first time, photolithography enabled by metasurface‐generated UV holograms is shown. Such performance enhancement is attributed to increased scattering cross sections of Si antennas in the UV range, which is adequately modeled via a circuit. The new platform introduced here will deepen the understanding of light–matter interactions and introduce even more material options to broadband metaphotonic applications, including those in integrated photonics and holographic lithography technologies. Abstract : Practical metasurfaces across the broadband ultraviolet range based on silicon, which was previously considered not useful in the ultraviolet, are demonstrated. High‐efficiency beam steering and photolithography enabled by metasurface‐generated ultraviolet holograms are achieved for the first time. Such performance enhancement is due to the large permittivity‐induced high scattering efficiency, which is well explained with a circuit model.